Keragaan Beberapa Varietas Pak Choi (Brassica rapa L. ssp. chinensis (L.)) pada Dua Jenis Larutan Hara dengan Metode Hidroponik Terapung - Wendy Yoditya Utomo; Eva Sartini Bayu; Isman Nuriadi (Jurnal Agroekoteknologi, 2014)
Pak choi (Brassica rapa L. ssp. chinensis (L.)) is a leaf vegetable which has a high commercialvalue. Pak choi generally grown in highlands with low temperatures. Lately, many farmers inlowland who interestedcultivate pak choi.Lowlands generally a densely populated area. Hydroponicis an appropriate technology that can be used in a confined area.This research aimed to look at somevarieties of pak choi performance in two kinds of nutrient solution with floating hydroponictechnology. The levels of varieties wereWhite Tropical, Green, and Green Tropica Corina andnutrient solutionswere Peckenpaugh and Resh. The treatments were arranged in split plotdesign(SPD) and each treatment was made in four repetition.The results showed that Peckenpaughnutrient gives better effect on number of leaves at 3 (6,40 strands)and 5 (6,83 strands) weeks afterplanted, and on fresh weight per sample (11,97 g). White Tropical variety gives better effect onfresh weight per sample (13,12 g)and chlorophyll content (19,88 unit/3.8-1”).Keyword: Pak choi, Varieties, Nutrients, Hydroponic